2010
DOI: 10.1007/s00018-010-0299-5
|View full text |Cite
|
Sign up to set email alerts
|

In front of and behind the replication fork: bacterial type IIA topoisomerases

Abstract: Topoisomerases are vital enzymes specialized in controlling DNA topology, in particular supercoiling and decatenation, to properly handle nucleic acid packing and cell dynamics. The type IIA enzymes act by cleaving both strands of a double helix and having another strand from the same or another molecule cross the DNA gate before a re-sealing event completes the catalytic cycle. Here, we will consider the two types of IIA prokaryotic topoisomerases, DNA Gyrase and Topoisomerase IV, as crucial regulators of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 189 publications
(247 reference statements)
1
76
0
1
Order By: Relevance
“…Ectopic expression of GyrB both of E. coli or B. schoenbuchensis unambiguously showed that these proteins are adenylylated by VbhT in bacterial lysates in vitro ( Figure 2D). Given the very high similarity in sequence, structure, and function to GyrB, we further suspected that its paralog ParE also might be targeted by VbhT (Sissi and Palumbo, 2010). Indeed, like for GyrB, ectopic expression of ParE of E. coli and B. schoenbuchensis clearly demonstrated adenylylation by VbhT ( Figure 2D).…”
Section: Ectopic Expression Of Diverse Ficts Results In Reversible Inmentioning
confidence: 90%
See 1 more Smart Citation
“…Ectopic expression of GyrB both of E. coli or B. schoenbuchensis unambiguously showed that these proteins are adenylylated by VbhT in bacterial lysates in vitro ( Figure 2D). Given the very high similarity in sequence, structure, and function to GyrB, we further suspected that its paralog ParE also might be targeted by VbhT (Sissi and Palumbo, 2010). Indeed, like for GyrB, ectopic expression of ParE of E. coli and B. schoenbuchensis clearly demonstrated adenylylation by VbhT ( Figure 2D).…”
Section: Ectopic Expression Of Diverse Ficts Results In Reversible Inmentioning
confidence: 90%
“…GyrB and ParE are the B subunits of the two bacterial type IIA topoisomerases DNA gyrase and topo IV that control cellular DNA topology by maintaining negative supercoiling and removing DNA catenation and knotting, respectively (Sissi and Palumbo, 2010). Therefore, their activities are generally essential for all processes in bacterial cells that involve the manipulation of closed circular DNA, such as chromosome replication, segregation, and transcription (Vos et al, 2011).…”
Section: Ectopic Expression Of Diverse Ficts Results In Reversible Inmentioning
confidence: 99%
“…ATP binding to the ATPase domain of the GyrB subunit causes N-gate closing and ensures directional transfer of the trapped DNA T-segment through the DNA-gate. Closure of the N-gate may also exert a pinching force that is mediated by the transducer domains on the trapped DNA segment to facilitate transfer through the DNA-gate [3]. It has been demonstrated that ATP hydrolysis occurs sequentially for yeast topoisomerase II [29].…”
Section: Discussionmentioning
confidence: 99%
“…For clarity, the coiled-coil and β-pinwheel domains of GyrA are omitted in (b-d). Adopted from references [3], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The gene duplication events that gave rise to these two complexes are very ancient, predating the split between Gram-negative and Gram-positive bacteria (e.g. Sissi & Palumbo, 2010). DNA gyrase and topoisomerase IV play important roles in DNA supercoiling and in the decatenation of closed circular DNA molecules.…”
Section: Quinolone Targets and Mechanisms Of Resistancementioning
confidence: 99%